2018
DOI: 10.3389/fphys.2018.01068
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in the Blood Labyrinthine Barrier in the Macula Utricle of Meniere’s Disease Patients

Abstract: The blood labyrinthine barrier (BLB) is critical in the maintenance of inner ear ionic and fluid homeostasis. Recent studies using imaging and histopathology demonstrate loss of integrity of the BLB in the affected inner ear of Meniere’s disease (MD) patients. We hypothesized that oxidative stress is involved in the pathogenesis of BLB degeneration, and to date there are no studies of oxidative stress proteins in the human BLB. We investigated the ultrastructural and immunohistochemical changes of the BLB in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 95 publications
5
24
0
3
Order By: Relevance
“…Recent progress on BLB pathophysiology in animal models highlights the importance of the BLB integrity for ion homeostasis, prompting us to question whether dysfunction of the BLB is key to understand the pathophysiology of MD (Shi, 2011, 2016; Hirose et al, 2014). We detected increased transcellular vesicular transport across VECs, detachment of pericyte processes, and disruption of perivascular basement membrane in the stroma beneath the macula and cristae vestibular sensory epithelia in MD patients (Ishiyama et al, 2017, 2018).…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…Recent progress on BLB pathophysiology in animal models highlights the importance of the BLB integrity for ion homeostasis, prompting us to question whether dysfunction of the BLB is key to understand the pathophysiology of MD (Shi, 2011, 2016; Hirose et al, 2014). We detected increased transcellular vesicular transport across VECs, detachment of pericyte processes, and disruption of perivascular basement membrane in the stroma beneath the macula and cristae vestibular sensory epithelia in MD patients (Ishiyama et al, 2017, 2018).…”
Section: Introductionmentioning
confidence: 86%
“…Our recent studies have demonstrated pathology of the BLB in MD (Ishiyama et al, 2017, 2018), a disabling inner ear disorder characterized by incapacitating attacks of vertigo, hearing loss, and tinnitus (Baloh, 2001; Ishiyama et al, 2001). Histopathological studies have demonstrated a nearly universally associated hydrops of the endolymphatic system of the inner ear, a ballooning of the endolymph structures (Hallpike and Cairns, 1938; Yamakawa, 1938; Schuknecht, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The protocol for microdissection of vestibular endorgans, 27 immunofluorescence, and immunohistochemistry in cryostat sections and whole endorgans has been described in detail. [27][28][29] The vestibular endorgans were immersed in 30% sucrose in PBS for 7 days for cryoprotection. Twenty-micron thick serial sections were obtained using a cryostat (Microm-HN505E).…”
Section: Antibodiesmentioning
confidence: 99%